Potensi Buah Andaliman (Zanthoxylum acanthopodium DC.) sebagai Antibakteri Terhadap Salmonella typhi - Helen Anjelina Simanjuntak; Hermawan Purba; Cander Pasaribu; Junius Gian Ginting; Rahmiati Rahmiati; Toberni S Situmorang (Mahesa Research Center, 2023)
Typhoid fever is a major disease of death in the medical field caused by Salmonella typhi infection with symptoms including fever, mucosal lesions, vomiting, diarrhea, fluid loss, septicemia, and peritonitis. The use of natural plants to cure infectious diseases such as andaliman fruit. The aim of this study was to determine the antibacterial activity of Andaliman fruit extract on the growth of Salmonella typhi. Experimental research method. The Kirby-bauer method was used for the antibacterial test, the maceration method was used for extraction. The results of phytochemical compounds found flavonoids, tanins, saponins, tannins, alkaloids steroids, and triterpenoids in simplicia and andaliman fruit extracts. All extracts have the potential to inhibit the growth of Salmonella typhi, with the diameter of the inhibition zone consisting of 10.04 mm, 12.22 mm, 15.46 mm and 16.68 mm in the strong category. These doses are 10%, 30%, 50%, and 70%. The analysis shows the potential of Andaliman fruit extract as an antibiotic in the treatment of typhoid fever.